E-Service Quality, E-Trust dan E-Customer Satisfaction Pada E-Customer Loyalty dari Penggunaan E-Wallet OVO - Dewi, Ni Putu Karunia; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research is a quantitative study with a causal relationship to determine the direct effect of e-service quality, e-trust on e-customer satisfaction, the direct effect of e-service quality, e-trust, e-customer satisfaction on e-customer loyalty and the indirect effect between e-service quality and e-trust on e-customer loyalty through e-customer satisfaction on users of the OVO e-wallet application. The benefits of this research are carried out to increase our understanding, provide information and knowledge needed to solve problems and make decisions. Data collection was carried out through a survey with a questionnaire in the form of a google form. The population in this study are those who have used the OVO e-wallet, regularly make payment transactions using OVO in the last 1 month, live in Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) and are at least 17 years old. The questionnaire collected 150 respondents using the formula (Hair et al., 2019). The sampling method used is non-probability sampling with purpose sampling technique, to test validity and reliability using SmartPLS software. Based on the results of the study, of the 7 accepted hypotheses, namely e-service quality has no positive effect on e-customer satisfaction, e-trust has an effect on e-customer satisfaction, e-service quality and e-trust have no effect on e-customer loyalty, e-customer satisfaction has no positive effect on e-customer loyalty. Keywords: E-Service Quality, E-Trust, E-Customer Satisfaction, E-Customer Loyalty